SULAM UMP programme shares importance of microbes in biotechnology industry - Mimi Rabita, Abdul Wahit (2023)
KUANTAN, 26 January 2023 - The entire world is affected by the emergence of the COVID-19 outbreak, and to date, 48.6 million people have been infected and claimed more than 6 million lives in just two years.